SCREENING BAKTERI AMILOLITIK DAN SELULOLITIK DARI LIMBAH SAGU (Screening of Amylolytic and Cellulolytic Bacteria From Sago waste) - Yanti, Nur Arfa; Munir, Asmawati (Jurnal BioWallacea, 2014)
Screening of indigenous bacteria from sago waste based on amylolytic and cellulolytic activity was done to obtain bacterial isolate having double activity, i.e. could to hydrolize of starch (amylolytic) and cellulose (cellulolytic). Screening amylolytic and cellulolytic bacteria was done based on amylolytic and cellulolytic activity on agar media. Determination of amylolytic activity on starch agar media was based on the presence of clear zone around the bacterial colony upon flooding with lugolâs iodine solution. Cellulolytic activity was determine based on the presence of clear zone around the bacterial colony on Carboxy methyl cellulose (CMC) agar upon flooding with congo red solution. Presence of a clear zone around the colony indicated starch and cellulose hydrolysis. The diameters of clear zone produced on CMC and starch agar were measured and used as an indication of the amylolytic and cellulolytic activities of the bacteria. The results of the screening based on amylolytic and cellulolytic activity showed that a number of 21 bacterial isolates that having both activities. LCA2 was the bacterial isolate with the highest amylolytic and cellulolytic activity as revealed by the size of clearing zone on both types of agar plates. The diameters of clear zone on starch and CMC agar were 4,98Â Â  and 3,65 cm2, respectively. Therefore, LCA2 isolate was bacterial isolate that potent for biconvertion sago hampas into value-added products. Keywords : Bacteria, Amylolytic, Cellulolytic, Sago waste.